Les mutations récentes de l’espace migratoire syro-libanais - Mohamed Kamel Doraï (Université de Provence, 2007)
Lebanon and Syria, both countries with a long migratory tradition, are becoming today host countries for an increasing number of migrants and refugees. To the migratory links between Lebanon and Syria - because of the numerous round trips of Syrian workers - it is necessary to add an increasing number of migrants for whom Syria is the front door of Lebanon, looking for more attractive wages and many of them hoping to enter Europe or other Western countries. As Syria exports its manpower to Lebanon, it is also becoming in its turn a receiving country. Alongside these migrants, one can note a significant influx of refugees and asylum seekers, mostly from Iraq, Somalia and Sudan, three countries characterized by long-lasting conflicts. These migrant populations of more and more diverse origins settle durably in the suburbs of the large Lebanese and Syrian cities and contribute to the development of these areas.